Characterization of GNSS amplitude scintillations over Addis Ababa during 2009–2013. Issue 8 (15th April 2017) - Akala, A.O.; Ejalonibu, A.H.; Doherty, P.H.; Radicella, S.M.; Groves, K.M.; Carrano, C.S.; Bridgwood, C.T.; Stoneback, R.A.
Highlights: At Addis Ababa, highest occurrences of scintillations were recorded in April and least in June. Scintillations over Addis Ababa were localized within the northern sky. Small-spatial scale depletions were more detrimental to GNSS signals at Addis Ababa. At Addis Ababa, EGNOS signals are also vulnerable during active months of scintillations. Abstract: This study characterizes GNSS amplitude scintillations over an African equatorial station: Addis Ababa (Lat 9.03°N, Lon 38.77°E, Mag. lat 0.18°N), Ethiopia during a five-year period (2009–2013). Scintillations were majorly localized within the hours of 2200–2400 LT. On a monthly basis, the highest occurrences of scintillation at Addis Ababa were recorded in April, and the lowest in June. Seasonally, the highest occurrences were recorded in equinoxes, and the lowest in June solstices. On a yearly scale, scintillations recorded the highest occurrences in 2012 and the lowest in 2009. Large proportions of the scintillations were localized within the northern sky of Addis Ababa. Supporting the characterization of the GNSS data with C/NOFS data, we noted that small-spatial scale density depletions are more detrimental to GNSS signals than their large-scale counterparts. Finally, EGNOS geostationary satellites' signals also scintillated steadily at Addis Ababa, with noticeable occurrences on the low elevation EGNOS satellite's (PRN 120) data. These events commenced around local sunset terminator, forming plateaus that vanished around local midnight.